Allosuppression: evidence for the involvement of both "noncytotoxic" and cytotoxic T cells. - Zamoyska, R; Waldmann, H (1984)
Allogeneic suppressor cells were generated by priming to a minor histocompatibility antigen. C57BL/10 female mice were primed to the male-specific minor transplantation antigen, H-Y. After boosting, anti-male-primed cells could potently suppress the secondary antibody response of male spleen cells in vitro. Anti-male suppressor cells were H-2-restricted, radiation-resistant T cells which could act on either T or B cells in the responding population. Mapping the restriction elements for anti-male suppressor cells revealed two distinct subpopulations of effector cells. The majority subpopulation was restricted to H-Y in the context of the H-2Db molecule. These cells were probably cytotoxic T cells as they were inhibited by culture of the suppressor cells in pyrilamide (a histamine receptor antagonist, which prevents the maturation of cytotoxic T cells from their precursors). The second subpopulation of suppressor cells was restricted to H-Y in the context of H-2K or I region-coded molecules. as neither H-2Kb nor H-2Ib molecules can act as restriction elements for anti-male-specific cytotoxic T cells, this subpopulations was almost certainly not composed of conventional cytotoxic cells. Furthermore, these cells were not affected by culture in pyrilamide. Together these two populations act to completely inhibit the anti-trinitrophenyl (TNP) plaque-forming cell response of male spleen cells in vitro.